PENGUKURAN KAPASITAS PERIKANAN CAKALANG ANTAR WAKTU DI MALUKU - Stevanus Marelly Siahainenia; Johanis Hiariey (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2020)
Skipjack tuna resources in Maluku waters are quite potential, so its management and utilization need to be a concern for sustainability of the skipjack resources and fishing industry. However, the nature of open access resources tends to lead to overcapacity in fishing. At this condition, how is the condition of the skipjack fishing industry in Maluku in terms of using fishing inputs? This study aims to measure the capacity of skipjack tuna fisheries over time. Using the Data Envelopment Analysis (DEA) approach, which is CRS in nature. Time series data were obtained form the government institutions, i.e the KKP and the DKP Maluku, and the fishery’s NGOs. The results show that during observations from 1996 to 2015, the eficient of inputs was found in DMU-1996 and DMU-2014. Thus, in the DMU-1998 and DMU-2014, there were indicative of an increase in fishing equipment followed by an increase in production, but the number of fishing efforts actually decreased. Conclude, that fishing input, effort and fishing gear were efficient in the DMU-1998 and DMU-2014. In both DMUs were indicative of an increase in fishing equipment followed by an increase in production, but the number of fishing efforts actually decreased.